Stimulation Effect of Exosome From Healthy Sera to Natural Killer (NK) Cells of Hepatocellular Carcinoma Subject In Vitro - Deby, Deby; Antarianto, Radiana Dhewayani; Barasila, Atikah Chalida; Irawan, Cosphiadi; Ahani, Ardhi Rahman; Jasirwan, Chyntia Olivia Maurine; Damayanti, Lia; Ritchie, Ni Ken; Aditya, Robby Nur (http://dharmais.co.id/, 2024)
Background: Hepatocellular carcinoma has a poor prognosis due to limitations of therapy such as late diagnosis, lack of specific biomarkers, and insensitivity to this tumor agent. This study aims to develop immunotherapy using autologous natural killer cells (NK cells) with exosome stimulation for hepatocellular carcinoma patients, addressing treatment limitations.Methods: Experimental research conducted from October 2022 to June 2023 at Universitas Indonesia’s Faculty of Medicine involved three hepatocellular carcinoma patients at Dr. Cipto Mangunkusumo General Hospital in Jakarta, Indonesia. NK cells from hepatocellular carcinoma patients were isolated from peripheral venous blood, and exosomes were isolated from the blood serum of healthy donors. Exosome characterization with a particle size analyzer and flow cytometry. Stimulation of exosomes on NK cells for 24 hours, then evaluation of expression of NKp44, NKp46, NKp30, NKG2D, KIR2D, and NKG2A receptors, as well as perforin and granzyme B expression. Visualization of interactions of NK cells with other mononuclear cell fractions (CD4, CD8, CD11c, and CD19) by immunofluorescence. The study compares stimulated and unstimulated NK cells, analyzing their expression of activated and inhibitory receptors, using either the One-Way Anova parametric test or the Kruskal-Wallis non-parametric test for non-normally distributed data.Results: Particle size 100 nm, negative electric charge, and CD63+CD81+ (double positive) exosome isolated results. There was increased expression of receptors NKp44, NKp46, NKp30, NKG2D, decreased expression of NKG2A, and increased expression of perforin and granzyme B in exosome-induced NK cells. There was no cell interaction in the form of immune synapses between exosome-induced NK cells and other mononuclear cell fractions in hepatocellular carcinoma patients. Conclusions: Induction of exosomes into NK cells of hepatocellular carcinoma patients restores the cytotoxic ability of NK cells